Geometrical and structural design development of an active-bending structure from natural fibre pultruded profiles: The LightPRO shell - Evgenia Spyridonos; Yanan Guo; Marta Gil Pérez; Hanaa Dahy (Developments in the Built Environment)
The utilisation of bio-based materials has significantly increased in recent years, driven by a growing awareness of environmentally friendly alternatives in the construction industry. This study introduces innovative natural fibre pultruded profiles for load-bearing applications in structural systems. By employing pultrusion technology with flax fibres and customised plant-based matrix, linear and unidirectional biocomposite profiles were developed. These profiles were used in the creation of LightPRO Shell, an active-bending structure combining biocomposite profiles with a membrane outer skin, demonstrating their mechanical properties and suitability for such applications. The paper focuses on the geometrical and structural design development of the structure employing computational design tools for optimisation, ensuring design parameters and performance requirements were met. The final structure, a 10-m span doubly curved gridshell, features a continuous perimeter beam and consists of 44 profiles ranging from 6 to 12.5 m, showcasing the potential of natural fibre biocomposites as sustainable alternatives in construction.